54.1k views
3 votes
Which equation written below in vertex form is equivalent to the equation?

Which equation written below in vertex form is equivalent to the equation?-example-1
User YjyJeff
by
4.6k points

1 Answer

6 votes

First, consider that a quadratic equation in vertex form is given by:


y=a(x-h)^2+k

where a is the leading coefficient and (h,k) is the vertex of the curve.

You have the following equation:


y=x^2-6x+12

In this case, the leading coefficient is a = 1.

The vertex is determined as follow:

Use the following formula to find h:


h=-(b)/(2a)=-(-6)/(2(1))=3

where we have used b = -6.

Now, to find k use:


f(h)=(3)^2-6(3)+12=9-18+12=3

Then, h = 3 and k = 3.

By replacing the values of a, h and k, you obtain:


y=(x-3)^2+3

The previous result is the given equation in vertex form.

User Andrew Sayer
by
4.6k points